Design fires in road tunnels - Maevski, Igor Y. (Synthesis of highway practice, 2011)
"TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 415: Design Fires in Road Tunnels information on the state of the practice of design fires in road tunnels, focusing on tunnel fire dynamics and the means of fire management for design guidance"--Publisher's description